MATCHING APPROACHES TO TEACHING WRITING FOR SECOND AND FOREIGN LANGUAGE LEARNERS - Ismaili Ismaili (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2016)
The present paper reviews some recent approaches which meet to the needs and the characteristics of second and foreign language learners in learning writing. Unlike teaching writing in first language context, teaching writing in second and foreign language context is more challenging and sometime faces more complicated problems. Therefore, teacher needs to use appropriate approach to overcome problem in his/her teaching. There are two different approaches presented in this paper: genre-based approach and lexical approach. Genre-based approach is considered effective due to its linguistic structure which provides learners with a clear idea of what language features should be expressed and how the content should be organized. On the other hand, language classroom which is organized by using lexical principles give the learners awareness to ‘chunk’ to form appropriate expression fluently and effortlessly. In conclusion, teaching writing to second and foreign language learners can’t only apply a single approach, method, or technique. Keywords: approaches, teaching writing, second and foreign language learners